The compatibility of running-based anaerobic sprint test and Wingate anaerobic test: a systematic review and meta-analysis - Kuldeep Nara (Pedagogy of Physical Culture and Sports, 2022)
Background and Study Aim. The objective of the study was to perform a systematic review of the literature and meta-analysis to determine the validity of running-based sprint test in relation to 30 second Wingate anaerobic test.